THE LYGEO-STIPETEA CLASS IN SICILY - BRULLO, C.; BRULLO, S.; GIUSSO DEL GALDO, G.; GUARINO, R.; MINISSALE, P.; SCUDERI, L.; SIRACUSA, G.; SCIANDRELLO, S.; SPAMPINATO, G. (Annali di Botanica, 2010)
Basing on literature data and unpublished relevés from Sicily, a survey of the syntaxa belonging to the class Lygeo-Stipetea Rivas-Martínez 1978 is presented. This perennial vegetation is characterized by the dominance of big caespitose hemicryptophytes, and it is widely distributed in Sicily from the sea level up to 1500 m a.s.l. The class is represented in Sicily by two orders, floristically and ecologically well differentiated: Lygeo-Stipetalia, including the sole alliance Moricandio-Lygeion exclusively of clayey substrates, and Hyparrhenietalia hirtae, including five alliances (Hyparrhenion hirtae, Avenulo cincinnatae-Ampelodesmion mauritanici, Thero-Brachypodion ramosi, Bromo-Oryzopsion miliaceae, and Arundion collinae) occurring on various substrates. Within the class, 50 associations have been recognized. To support the syntaxonomic proposal, a multivariate numerical analysis, considering literature and personal data, has been performed. Nomenclature, floristic settlement, ecology, syndynamism and chorology are examined for each syntaxon.